2001
DOI: 10.1034/j.1600-0420.2001.790320.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous blood injection for marked overfiltration early after trabeculectomy with mitomycin C

Abstract: ABSTRACT.Purpose: After trabeculectomy with mitomycin C, extremely low intraocular pressure (IOP) with excess filtration may cause hypotonous maculopathy in the early postoperative period. We evaluated the effect of injecting autologous blood on reversing early postoperative marked hypotony after trabeculectomy with mitomycin C. Methods: Trabeculectomy with mitomycin C was performed in 258 eyes between 1994 and 1998. Peribleb autologous blood injection was performed in five eyes in which pressure patches were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…While innovations in MMC dosage and application have improved bleb morphology, bleb-related complications are still seen. Nonsurgical methods of bleb revision include injection of autologous blood serum to stimulate scarring and thereby reduce bleb height, but studies have reported variable results [15][16][17][18][19][20] and complications, including bleb failure, have been reported with this technique. [21][22][23][24] Laser treatments have been used but may require multiple sessions that can induce inflammation and ultimately lead to less predictable IOP control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While innovations in MMC dosage and application have improved bleb morphology, bleb-related complications are still seen. Nonsurgical methods of bleb revision include injection of autologous blood serum to stimulate scarring and thereby reduce bleb height, but studies have reported variable results [15][16][17][18][19][20] and complications, including bleb failure, have been reported with this technique. [21][22][23][24] Laser treatments have been used but may require multiple sessions that can induce inflammation and ultimately lead to less predictable IOP control.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the study eyes were from White patients (13 eyes, 54.5%), while Black (5 eyes, 21.7%), Hispanic (4 eyes, 17.4%), and Asian (1 eye, 4.3%) eyes comprised the remaining participants. Reasons for ologen revision included persistent bleb leak with low IOP (18), dysesthesia (3), and an overfiltering bleb (2). Two eyes with dysesthesia and one eye with a bleb leak also demonstrated an overhang of the avascular bleb onto the cornea.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Okada et al performed peri-bleb injections of autologous blood in five eyes with excess filtration and hypotony after trabeculectomy, but without hypotony maculopathy. After a mean 31-month follow-up, all eyes had well-controlled IOP while visual acuity in three eyes was much improved [39]. Due to small sample size and no rigorous methodology, further research is needed to establish the best surgical approach for these patients and the long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Maculopathy due to hypotony is a rare complication of glaucoma filtering surgery, trauma, and other anterior segment procedures. It was uncommon prior to the advent of adjunctive antifibrotic agents for glaucoma surgery [6,7].…”
Section: Introductionmentioning
confidence: 99%